Mammalian target of rapamycin pathway mutations cause hemimegalencephaly and focal cortical dysplasia. Issue 4 (26th February 2015) - D'Gama, Alissa M.; Geng, Ying; Couto, Javier A.; Martin, Beth; Boyle, Evan A.; LaCoursiere, Christopher M.; Hossain, Amer; Hatem, Nicole E.; Barry, Brenda J.; Kwiatkowski, David J.; Vinters, Harry V.; Barkovich, A. James; et al.
Abstract : Focal malformations of cortical development, including focal cortical dysplasia (FCD) and hemimegalencephaly (HME), are important causes of intractable childhood epilepsy. Using targeted and exome sequencing on DNA from resected brain samples and nonbrain samples from 53 patients with FCD or HME, we identified pathogenic germline and mosaic mutations in multiple PI3K/AKT pathway genes in 9 patients, and a likely pathogenic variant in 1 additional patient. Our data confirm the association of DEPDC5 with sporadic FCD but also implicate this gene for the first time in HME. Our findings suggest that modulation of the mammalian target of rapamycin pathway may hold promise for malformation‐associated epilepsy. Ann Neurol 2015;77:720–725